2022
DOI: 10.21203/rs.3.pex-1653/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

REBOA and its effect on hemodynamics and cerebral blood flow as measured by CTP in a large animal model of raised intracranial pressure and hemorrhagic shock.

Abstract: Hemorrhage is among the leading causes of preventable deaths in trauma. Further traumatic brain injury (TBI) often present in a polytrauma patient, and is known to worsen outcomes when present with non compressible torso hemorrhage (NCTH). Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been developed as a means of hemorrhage control and afterload increase during a state of hemorrhagic shock, but its use in patients with both hemorrhagic shock and concomitant TBI is controversial, as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… Stonko et al, 2022a ; Cannon et al, 2018 ; Khan and McMonagle, 2019 ; Vella et al, 2019 ; Wasicek et al, 2019 ; Stonko et al, 2022e REBOA, however, is contingent on spontaneous circulation. To achieve spontaneous circulation during ECA, the current practice is to perform CPR with a REBOA in place, but previous studies have shown that the use of CPR is terrible for brain perfusion ( Abdou et al, 2022 ; Patel et al, 2022b ; Edwards et al, 2022 ). Therefore, other methods, such as SAAP and ECMO, may be better alternatives to CPR in the absence of spontaneous circulation.…”
Section: Discussionmentioning
confidence: 99%
“… Stonko et al, 2022a ; Cannon et al, 2018 ; Khan and McMonagle, 2019 ; Vella et al, 2019 ; Wasicek et al, 2019 ; Stonko et al, 2022e REBOA, however, is contingent on spontaneous circulation. To achieve spontaneous circulation during ECA, the current practice is to perform CPR with a REBOA in place, but previous studies have shown that the use of CPR is terrible for brain perfusion ( Abdou et al, 2022 ; Patel et al, 2022b ; Edwards et al, 2022 ). Therefore, other methods, such as SAAP and ECMO, may be better alternatives to CPR in the absence of spontaneous circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary flows are measured continuously and recorded in microseconds, though extracted in 5 ms increments. The pressure-volume loops are generated with a micromanometer tipped catheter (Transonic Corporation, Ithaca, NY) and computed with the admittance method ( Johnson et al, 2017 ; Edwards et al, 2022 ). PV loop data was recorded in pressure versus volume versus time data with LabChart, and exported to MATLAB (Mathworks, Nantick, MA, United States).…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…LabChart analyzes each PV loop, which corresponds to one cardiac cycle, for hemodynamic parameters such as stroke work, heart rate, and measures of preload, afterload and ( Heindl et al, 2020 ; Edwards et al, 2022 ) contractility over time. We have previously described methodology for averaging the PV loop over a time period to determine a single PV loop that is representative of LV function during that time period, and published Matlab code to execute this procedure ( Edwards et al, 2022 ). In summary of the mathematical methodology, we convert raw pressure-volume data to polar coordinates, interpolate numerous cardiac cycle loops, then convert back to cartesian coordinates.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation